Community-driven educational and training model for sustainable community development resulting in sosio-economic upliftment in the Western Soutpansberg - Rosmarin, Tessa (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--Stellenbosch University, 2008.